Unemployment among youth: Causes and its psychological implication / Raja Zirwatul Aida Raja Ibrahim, Madihah Mohamad Shukri and Azlina Abu Bakar@ Mohd - Raja Ibrahim, Raja Zirwatul Aida; Mohamad Shukri, Madihah; Abu Bakar@ Mohd, Azlina (2004)
With the world's major economies slowing down and threatening the growth prospects of developing countries, the unemployment of youth - those between the ages 15 and 24 - who account for 41 percent of the world's unemployed, is becoming a focus for United Nations concerted action. Youth unemployment rates are typically two to three times higher than the adult rates, and are alarmingly high in many countries. The paper looks at the global issue of unemployment but focuses on unemployment among youth. Causes of unemployment are multifactorial. However, the study will lokk in depth to the character and attitudes of the young and employers, the higher skill and educational requirements for many occupations and the fact that general downturns in the overall demand for labor have a disproportionate influence on new entrants to the workforce, so that cyclical fluctuations in youth unemployment are marked. Effects and consequences of unemployment will cover in term of psychological effects which are severe in younger group. Cross sectional and longitudical studies (including longitudinal studies of young Australians) have consistently found poorer psychological health in unemployed compared with employed people. How the unemployment affects youth's self esteem, locus of control and mood states will be discussed. Besides, if it does not being dealt successfully, it will leads to depression and helplessness. Survey among unemployed youth was conducted among 100 unemployed youth in Kuala Terengganu. It also discusses on how counseling deals with unemployment as the whole and the effectiveness of career counseling in helping unemployed youth in Malaysia and other countries will be previewed and compared. The findings of the study have numerous implications that give understanding to the unemployment phenomenon and can be used for policy recommendations.